Analisis Bibliometrik pada Penelitian Diplomasi Digital - Syuryansyah; Waskito, Wasis; Setiawan, Roy (UIN ALAUDDIN MAKASSAR, 2024)
This study conducted a bibliometric analysis in the field of digital diplomacy. The authors utilized Publish or Perish (PoP) software for descriptive data analysis, using Google Scholar and Crossref as the database sources. The collected data were stored in RIS format using Mendeley for research mapping with VOSViewer. The study found that papers published in reputable journals indexed by Scopus had a more significant impact compared to those in non-Scopus journals. Furthermore, articles published in Scopus-indexed journals tended to receive more citations. The research successfully identified potential research topics for further exploration based on less commonly used keywords in the literature on digital diplomacy. Consequently, this study provides valuable insights into the development of the digital diplomacy field and offers guidance for researchers to explore intriguing areas with the potential for significant contributions.